Nurturing Hearts and Minds: Teachers’ Experiences in Enhancing Learners Socio-Emotional Health Through the Homeroom Guidance Program - Caparas, Vergie May N.; Baysa, Marilyn L (Edu Berkah Khatulistiwa, 2025)
This study aimed to explore the lived experiences of teachers in nurturing the hearts and minds and enhancing the socio-emotional health of learners through Homeroom Guidance Program. This study explored the lived experiences of Grade 4 teachers in nurturing students’ hearts and minds and enhancing their socio-emotional well-being through the Homeroom Guidance Program (HGP). The research involved ten Grade 4 teachers from public elementary schools in the Division of Cabuyao during the 2024–2025 school year. Utilizing a transcendental phenomenological approach, data were gathered through semi-structured interview guides to investigate the teachers’ practices in promoting socio-emotional health among learners. The participants’ responses were validated and analyzed with the assistance of a qualitative data analyst. The findings revealed that the HGP plays a crucial role in the holistic development of Grade 4 learners and is perceived by teachers as an integral part of their teaching responsibilities. Teachers emphasized the importance of linking real-world situations to HGP activities, using them as entry points to deepen students’ understanding of various life issues. However, challenges such as students’ behaviors and attitudes were found to hinder the full implementation and impact of the program. In response, teachers addressed these challenges by actively listening to students’ experiences and implementing instructional strategies tailored to diverse learning needs. Nine key themes emerged from the participants’ narratives, highlighting both internal and external challenges in supporting socio-emotional development. Teachers provided learners with opportunities for self-expression and collaborative activities to foster peer interaction and socio-emotional growth. Differentiated instruction was identified as a core strategy for addressing student diversity and promoting well-being. Based on these findings, the study recommends that school heads conduct quarterly roundtable discussions with teachers and guidance coordinators to address issues related to the HGP and to act promptly on students’ socio-emotional concerns. Teachers are encouraged to incorporate more group-based learning to build students’ confidence and peer support. Guidance counselors are advised to regularly consult with students to identify and address socio-emotional needs and behavioral concerns. Lastly, the implementation of differentiated instruction should be prioritized, with regular reporting to the guidance office to inform the development of responsive school policies and programs.